A regression model for analysing the non-linearity of laser triangulation probes - Dong, Chensong (Springer London, 2011)
A study on the non-linearity of laser triangulation probes is presented in this paper. The influences of design variables on non-linearity were studied by response surface methodology, and the significant factors were identified. A regression model was developed with which non-linearity can be conveniently evaluated in the design stage of laser triangulation probes. The sensitivities of non-linearity to the design variables are evaluated.